Development of a chemical scaffold for inhibiting nonribosomal peptide synthetases in live bacterial cells - Ishikawa, Fumihiro; Konno, Sho; Kakeya, Hideaki; Tanabe, Genzoh (Beilstein Journal of Organic Chemistry, 2024)
The adenylation (A) domain is essential for non-ribosomal peptide synthetases (NRPSs), which synthesize various peptide-based natural products, including virulence factors, such as siderophores and genotoxins. Hence, the inhibition of A-domains could attenuate the virulence of pathogens. 5’-O-N-(Aminoacyl or arylacyl)sulfamoyladenosine (AA-AMS) is a bisubstrate small-molecule inhibitor of the A-domains of NRPSs. However, the bacterial cell permeability of AA-AMS is typically a problem owing to its high hydrophilicity. In this study, we investigated the influence of a modification of 2′-OH in the AMS scaffold with different functional groups on binding to target enzymes and bacterial cell penetration. The inhibitor 7 with a cyanomethyl group at 2′-OH showed desirable inhibitory activity against both recombinant and intracellular gramicidin S synthetase A (GrsA) in the gramicidin S-producer Aneurinibacillus migulanus ATCC 9999, providing an alternative scaffold to develop novel A-domain inhibitors.
Keywords: adenylation domain inhibitor; gramicidin S synthetase; natural product; nonribosomal peptide; nonribosomal peptide synthetase